2016
DOI: 10.1242/dev.134270
|View full text |Cite
|
Sign up to set email alerts
|

G2-phase arrest prevents bristle progenitor self-renewal and synchronizes cell divisions with cell fate differentiation

Abstract: Developmentally regulated cell cycle arrest is a fundamental feature of neurogenesis, whose significance is poorly understood. During Drosophila sensory organ (SO) development, primary progenitor ( pI) cells arrest in G2 phase for precisely defined periods. Upon reentering the cell cycle in response to developmental signals, these G2-arrested precursor cells divide and generate specialized neuronal and non-neuronal cells. To study how G2 phase arrest affects SO lineage specification, we forced pI cells to divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Loss of stg , w ee1 or m yt1 expression does not affect the timing of the first division of SOPs ( Fig. 3 A-C) (which are subject to additional regulation; Ayeni et al, 2016 ). Together, these results support a model in which the opposing activities of Cdc25 and Wee1/Myt1 regulate EC division timing.…”
Section: Resultsmentioning
confidence: 97%
“…Loss of stg , w ee1 or m yt1 expression does not affect the timing of the first division of SOPs ( Fig. 3 A-C) (which are subject to additional regulation; Ayeni et al, 2016 ). Together, these results support a model in which the opposing activities of Cdc25 and Wee1/Myt1 regulate EC division timing.…”
Section: Resultsmentioning
confidence: 97%
“…It is reasonable that sevoflurane may affect G1-phase in different cell types through different mechanisms. Altered G2- and M-phase duration has been reported to directly alter cell fate in neural progenitors [ 44 , 45 ], but the effect of sevoflurane on these two cell cycle phases of neural progenitors has not yet been studied in detail. In the present study, we did not find any significant differences in the expression of PH3 (Figures 6(e) and 6(f) ), an indicator of M-phase and late G2-phase [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A developmentally regulated G2 arrest is essential for proper cell fate decisions in sensory organ precursors (SOPs), as disruption of proper Cdk1 activity in SOPs can alter cell division timing and asymmetric cell fate decisions (Fichelson and Gho 2004;Ayeni et al 2016). Consistent with this, we observed that inhibition of Cdk1 activity was sufficient to fully recapitulate the ectopic neuron phenotype in the posterior wing margin, similar to that observed when components of the DREAM or the Myb component of MMB are inhibited (Rovani et al 2012) (Figures 6F and Figure 7, E and F).…”
Section: Nua4 Inhibition Does Not Delay Cell Cycle Exit Through the Pmentioning
confidence: 99%